Pengenalan Potensi, Budaya dan Pariwisata Kabupaten Brebes Berbasis Android Menggunakan Metode Disciplined Agile Delivery - Merry Shovita Rizkiana; Fahrudin Mukti W; Yudha Saintika (LPPM INSTITUT TEKNOLOGI TELKOM PURWOKERTO, 2020)
The diversity of natural potentials and cultural traditions in Indonesia is a wealth that needs to be known and preserved. One culture that is still maintained up to now is in Brebes Regency, the Jalawastu Tradition. In addition to cultural diversity, Brebes Regency also has other potential, namely, natural tourism, historical heritage that is still preserved. From the diversity of these assets, adequate information facilities are needed in order to facilitate the wider community in recognizing the gap of Indonesia, especially in Brebes Regency which is still minimal. Efforts are made to introduce this matter is to make a container to hold that information. Android mobile-based technology was chosen as an innovation to introduce the diversity of potential and culture in a more efficient and simple way. To make this application also requires a method that can make this system can be done with a sequence of stages and the right time, so that this system can be used by the whole community and tourists.